2009
DOI: 10.1111/j.1471-0374.2009.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Small is beautiful: the micro‐politics of transnational relationships between Ghanaian hometown associations and communities back home

Abstract: In this article we investigate why some hometowns in Ghana are more successful than others in mobilizing resources for community development projects from their hometown associations (HTAs) abroad. We analyse the praxis of HTA‐financed development by studying all actors involved in the process – HTAs and migrants abroad and local community leaders and their populations in Ghana. We find there is a relationship between the size of the community and the effectiveness of HTA mobilization. From a matched sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…However, McIlwaine (2007McIlwaine ( : 1274 argues that this celebration of 'diasporic civil society' as 'a potential development saviour' has been based on rather limited knowledge. As Mazzucato and Kabki (2009) assert, there are few studies that combine a substantive focus on diaspora organisations with an empirical exploration of their sites of intervention at 'home'. Indeed, where diaspora organisations and their border-spanning activities are addressed, it tends to be within wider studies of migrant transnationalism in which they do not constitute the specific focus of research.…”
Section: Introduction: Constructing and Questioning Collective Transnmentioning
confidence: 99%
“…However, McIlwaine (2007McIlwaine ( : 1274 argues that this celebration of 'diasporic civil society' as 'a potential development saviour' has been based on rather limited knowledge. As Mazzucato and Kabki (2009) assert, there are few studies that combine a substantive focus on diaspora organisations with an empirical exploration of their sites of intervention at 'home'. Indeed, where diaspora organisations and their border-spanning activities are addressed, it tends to be within wider studies of migrant transnationalism in which they do not constitute the specific focus of research.…”
Section: Introduction: Constructing and Questioning Collective Transnmentioning
confidence: 99%
“…However, while efforts to link migration with a development agenda have a long history, there are still significant debates over the impact of migration on communities of origin [9]. Notably, scholars have shown that migrant-led development projects are highly variable and are always shaped by local economic, social, and political contexts [6,10].…”
Section: Open Accessmentioning
confidence: 99%
“…There is also increasing recognition that local governments and migrant organizations are crucial to development outcomes [5,6]. In particular, hometown associations are viewed as an important source of remittances and knowledge of local conditions [7,8].…”
Section: Open Accessmentioning
confidence: 99%
“…Examples are migrant organizations that assist in repatriation of the deceased. Migrants often prefer to be buried in the country of origin, which is a costly and complex practice for families, as it requires extensive paperwork and knowledge of the system (Mazzucato and Kabki 2009 ). Lacroix ( 2010a ) describes how in France the organizations of Algerian Kabyle fulfi lled this role to build a bridge between the host society and the region of origin.…”
Section: Characterizing the Transnational Activities Of Migrant Organmentioning
confidence: 99%
“…This may range from advocacy work to 5 See also Mazzucato and Kabki ( 2009 ) electoral participation and features strong affi liation with particular political parties and a questioning of governance systems. Several political parties in origin countries have established branch organizations in countries of destination to reach out to the diasporas.…”
Section: Characterizing the Transnational Activities Of Migrant Organmentioning
confidence: 99%